2009
DOI: 10.1002/cncr.24542
|View full text |Cite
|
Sign up to set email alerts
|

Why cancer at the primary site and in the lymph nodes contributes to the risk of cancer death

Abstract: BACKGROUND:Cancer at both the primary site and in the lymph nodes is associated with lethality, although the mechanism by which lethality arises from each site has been poorly understood. For breast carcinoma, each positive lymph node contributes an approximately 6% risk of death, and each millimeter of primary tumor greatest dimension contributes approximately 1%; whereas, for melanoma, each positive lymph node contributes an approximately 23% risk, and each millimeter of tumor thickness contributes approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…Lymph node metastases (LNM), which contribute to the risk of cancer death (3), are found in approximately 7.45% of HCC patients (4). We have reported that LNM in HCC is sensitive to external beam radiotherapy (5), but the quality of life and survival of patients who undergo this procedure remains unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…Lymph node metastases (LNM), which contribute to the risk of cancer death (3), are found in approximately 7.45% of HCC patients (4). We have reported that LNM in HCC is sensitive to external beam radiotherapy (5), but the quality of life and survival of patients who undergo this procedure remains unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…Note that we have framed the definition of p x so that it does not consider events of spread that do not lead to a macroscopic manifestation, nor does this definition assume that p x is constant, 3,7,8 nor does it require that every cell in the mass of cancer have the potential for spread, although this may be the case. For further discussion, see the accompanying article this series and the report by Michaelson et al 7,8 Because p x is the probability of a single successful event of lethal spread, the probability per cell that there will not be an event of spread is (1 À p x ), and the overall probability that a tumor of N cells will not give rise to 1 or more lethal metastases will be (1 À p x ) N .…”
Section: Datamentioning
confidence: 99%
“…We also examine the relation between primary tumor size and the risk of cancer in the lymph nodes for breast carcinoma and melanoma. In the accompanying articles, we extend these finding to examine the reason for the lethal contributions of cancer at the primary site and in the lymph nodes, 8 the impact of prognostic factors other than primary tumor size and lymph node status on the risk of cancer death, 9 and the application of these finding to the development of web-based calculators that physicians can use to estimate the risk of cancer death (available at: http://www.CancerMath.net accessed on July 29, 2009). 9 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CancerMath.net). 5,6 Our analysis, outlined in a technical report available at the CancerMath.net website, indicates that the outcome predictions provided by both our melanoma calculator, and that of Soong et al, accurately predict the chance of survival, as tested against the Surveillance, Epidemiology, and End Results (SEER) melanoma national dataset provided by the National Cancer Institute. 7 However, as noted previously, the calculator developed by Soong et al sorts patients into rather large bins, which contain mixes of patients with widely disparate risks of death.…”
mentioning
confidence: 90%